Community Resilience of Sidanegara Village in Facing Covid-19 Pandemic in 2020 - Fajriyah, Nur; Noviani, Rita; Yusup, Yasin (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
As a national disaster, COVID-19 pandemic has impacted all parts of Indonesia in various fields, directly or indirectly. It’s even felt to smallest administrative area, including Sidanegara Village, in Kedungreja District, Cilacap Regency. This study aims to determine (1) the moment of spread of COVID-19 in Sidanegara Village, (2) level of community resilience in Sidanegara Village in face of COVID-19 pandemic. This study used qualitative description method with data on spread COVID-19 moment using interactive analysis technique of Miles and Huberman model, while data of community resilience level used scoring analysis technique. Results and conclusions of this study are (1) moment of COVID-19 spread in Sidanegara Village is divided into three, namely moment of the initial development of COVID-19 in Indonesia, moment of implementation of policies related to COVID-19, and moment towards New Normal, (2) level of community resilience in Sidanegara Village facing the COVID-19 pandemic are moderate level of resilience with score 12.6.